Promoting Social Inclusion and Mitigating Anxiety in Educational Settings through Self-Esteem: A Multi-Group PLS-SEM Analysis of College Students in Indonesia - Syamsuyurnita Syamsuyurnita; Faisal Rahman Dongoran; Reza Aditia (AL-ISHLAH: Jurnal Pendidikan, 2023)
This comprehensive study explores the predictive role of self-esteem in relation to anxiety, specifically trait anxiety and state anxiety. The research encompasses 229 college students from a university in Medan, Indonesia, who participated in an online survey. Utilizing Multi-Group Analysis PLS-SEM, the collected data underwent thorough analysis. The outcomes obtained from partial least squares structural equation modeling demonstrate that self-esteem has a negative impact on students' anxiety levels, encompassing both trait anxiety and state anxiety. Furthermore, the structural model was assessed across two distinct gender groups (Group 1: Female; Group 2: Male), and the results indicate the model's consistency across these groups. This study contributes novel insights to the existing literature on anxiety mitigation within educational contexts, particularly among Eastern populations. In conclusion, the findings emphasize the crucial role of self-esteem as a predictor of anxiety among college students in Indonesia. The research highlights a negative association between self-esteem and both trait anxiety and state anxiety. Additionally, by demonstrating the robustness of the structural model across gender groups, the study implies the universal implications of its findings. Overall, this research provides valuable insights for educators and practitioners seeking to address anxiety-related concerns and enhance the well-being of students in educational settings.